Immigrant IBD Patients in Spain Are Younger, Have More Extraintestinal Manifestations and Use More Biologics Than Native Patients - Gutiérrez, Ana; Zapater, Pedro; Ricart, Elena; González-Vivó, María; Gordillo, Jordi; Olivares, David; Vera, Isabel; Mañosa, Míriam; Gisbert, Javier P.; Aguas, Mariam; Sánchez-Rodríguez, Eugenia; Bosca-Watts, Maia; et al. (Frontiers in Medicine, 2022)
Background Previous studies comparing immigrant ethnic groups and native patients with IBD have yielded clinical and phenotypic differences. To date, no study has focused on the immigrant IBD population in Spain. Methods Prospective, observational, multicenter study comparing cohorts of IBD patients from ENEIDA-registry who were born outside Spain with a cohort of native patients. Results We included 13,524 patients (1,864 immigrant and 11,660 native). The immigrants were younger (45 ± 12 vs. 54 ± 16 years, p < 0.001), had been diagnosed younger (31 ± 12 vs. 36 ± 15 years, p < 0.001), and had a shorter disease duration (14 ± 7 vs. 18 ± 8 years, p < 0.001) than native patients. Family history of IBD (9 vs. 14%, p < 0.001) and smoking (30 vs. 40%, p < 0.001) were more frequent among native patients. The most prevalent ethnic groups among immigrants were Caucasian (41.5%), followed by Latin American (30.8%), Arab (18.3%), and Asian (6.7%). Extraintestinal manifestations, mainly musculoskeletal affections, were more frequent in immigrants (19 vs. 11%, p < 0.001). Use of biologics, mainly anti-TNF, was greater in immigrants (36 vs. 29%, p < 0.001). The risk of having extraintestinal manifestations [OR: 2.23 (1.92–2.58, p < 0.001)] and using biologics [OR: 1.13 (1.0–1.26, p = 0.042)] was independently associated with immigrant status in the multivariate analyses. Conclusions Compared with native-born patients, first-generation-immigrant IBD patients in Spain were younger at disease onset and showed an increased risk of having extraintestinal manifestations and using biologics. Our study suggests a featured phenotype of immigrant IBD patients in Spain, and constitutes a new landmark in the epidemiological characterization of immigrant IBD populations in Southern Europe.